2022
DOI: 10.1186/s12989-022-00479-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vitro digested zinc oxide nanoparticles on intestinal model systems

Abstract: Background Zinc oxide nanoparticles (ZnO NP) offer beneficial properties for many applications, especially in the food sector. Consequently, as part of the human food chain, they are taken up orally. The toxicological evaluation of orally ingested ZnO NP is still controversial. In addition, their physicochemical properties can change during digestion, which leads to an altered biological behaviour. Therefore, the aim of our study was to investigate the fate of two different sized ZnO NP (< 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Mitochondrial membrane potential (Δψm), an essential for ATP synthase to make ATP, is established by the proton transfer against their concentration gradient driven by the respiratory electron transport chains in the inner mitochondrial membrane [ 40 ]. It has been reported that the loss of Δψm could lead to the release of apoptotic factors, such as cytochrome C, and activate downstream apoptotic pathways [ 41 ]. JC-1, as a lipophilic cationic dye, was selectively capable of entering into mitochondria and reversibly changing its color from red to green when the Δψm decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial membrane potential (Δψm), an essential for ATP synthase to make ATP, is established by the proton transfer against their concentration gradient driven by the respiratory electron transport chains in the inner mitochondrial membrane [ 40 ]. It has been reported that the loss of Δψm could lead to the release of apoptotic factors, such as cytochrome C, and activate downstream apoptotic pathways [ 41 ]. JC-1, as a lipophilic cationic dye, was selectively capable of entering into mitochondria and reversibly changing its color from red to green when the Δψm decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found negative biological effects, such as increased intestinal inflammation, reduced cell viability, and mitochondrial membrane depolarization, resulting from the treatment with ZnO NPs. However, modified ZnO NPs do not cause significant cell damage [76,77].…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 99%
“…Such juices have been widely used for NM digestion. 2,8,[18][19][20][21] The "cascade in vitro digestion assay" is acknowledged as the most popular static assay, which simulates the passage of the NF within the OGI tract under fasting conditions through the sequential addition of simulated saliva, stomach and intestine. 2,8,19,[22][23][24] This assay allows the dissolution kinetics of NFs in semi-realistic environments (cascade addition of biomacromolecules and salts simulating the molecular compositions of the digestive juices and drastic changes in pH values and digestive volumes according to human physiology) to be studied.…”
Section: Introductionmentioning
confidence: 99%